Impact of dietary oxidized protein on oxidative status and performance in growing pigs. (27th March 2020) - Frame, Carl A; Johnson, Erika; Kilburn, Logan; Huff-Lonergan, Elisabeth; Kerr, Brian J; Serao, Mariana Rossoni
Abstract: Rendered products from the meat industry can provide economical quality sources of proteins to the animal and feed industry. Similar to lipids, rendered proteins are susceptible to oxidation, yet the stability of these proteins is unclear. In addition, interest in understanding how oxidative stress can impact efficiency in production animals is increasing. Recent studies show that consumption of oxidized lipids can lead to a change in the oxidative status of the animal as well as decreases in production efficiency. To date, little is known about how consumption of oxidized proteins impacts oxidative status and growth performance. The objectives of this study were to determine if feeding diets high in oxidized protein to growing pigs would: 1) impact growth performance and 2) induce oxidative stress. Thirty pigs (42 d old; initial body weight [BW ] 12.49 ± 1.45 kg) were randomly assigned to one of three dietary treatments with increasing levels of oxidized protein. Spray-dried bovine plasma was used as the protein source and was either unheated upon arrival, heated at 45 °C for 4 d, or heated at 100 °C for 3 d. Diets were fed for 19 d and growth performance was measured. Blood plasma (days 0 and 18), jejunum, colon, and liver tissues (day 19) were collected to analyze for markers of oxidative stress (e.g., protein oxidation, lipid oxidation, DNA damage, and glutathione peroxidase activity). Average daily gain (ADG; P < 0.01) and average daily feed intake (ADFI; P < 0.01) had a positive linear relationship to increased protein oxidation, but there was no effect on gain to feed ratio. Furthermore, protein ( P = 0.03) and fat ( P < 0.01) digestibility were reduced with increased protein oxidation in the diet. Crypt depth showed a positive linear relationship with dietary protein oxidation levels ( P = 0.02). A trend was observed in liver samples where pigs fed the plasma heated to 45 °C had increased lipid oxidation compared with pigs fed the plasma either unheated or heated to 100 °C ( P = 0.09). DNA damage in the jejunum tended to have a linear relationship with the dietary protein oxidation level ( P = 0.07). Even though results suggest dietary oxidized protein did not induce oxidative stress during short-term feeding, differences in performance, gut morphology, and digestibility are likely a result of reduced protein availability.